Massage for Children Undergoing Hematopoietic Cell Transplantation: A Qualitative Report. (23rd February 2012) - Ackerman, Sara L.; Lown, E. Anne; Dvorak, Christopher C.; Dunn, Elizabeth A.; Abrams, Donald I.; Horn, Biljana N.; Degelman, Marcia; Cowan, Morton J.; Mehling, Wolf E.
Abstract : Background . No in-depth qualitative research exists about the effects of therapeutic massage with children hospitalized to undergo hematopoietic cell transplantation (HCT). The objective of this study is to describe parent caregivers' experience of the effects of massage/acupressure for their children undergoing HCT. Methods . We conducted a qualitative analysis of open-ended interviews with 15 parents of children in the intervention arm of a massage/acupressure trial. Children received both practitioner and parent-provided massage/acupressure. Results . Parents reported that their child experienced relief from pain and nausea, relaxation, and greater ease falling asleep. They also reported increased caregiver competence and closeness with their child as a result of learning and performing massage/acupressure. Parents supported a semistandardized massage protocol. Conclusion . Massage/acupressure may support symptom relief and promote relaxation and sleep among pediatric HCT patients if administered with attention to individual patients' needs and hospital routines and may relieve stress among parents, improve caregiver competence, and enhance the sense of connection between parent and child.